Case report: Malignant epithelioid angiosarcoma in a Chinese female patient - Li, Xiaohong; Chen, Lu; Ye, Rong; Wu, Chunyan; Zhuo, Wenlei (Frontiers in Oncology, 2024)
Perivascular epithelioid cell tumors (PEComas) are mesenchymal tumors that exhibit characteristic epithelioid or spindle cell morphology and typically grow around blood vessels. These tumors are characterized by the expression of melanocytic and smooth muscle markers, such as HMB-45, Melan-A, and smooth muscle actin, indicating a dual differentiation phenotype. PEComas are extremely rare diseases, and patients typically have a very poor prognosis. Here, we report a case of malignant cutaneous PEComa with pulmonary metastasis and review relevant literature. The patient underwent surgical resection of a soft tissue tumor in the left upper arm under general anesthesia, and the subsequent pathological findings suggested a tumor with perivascular epithelioid cell differentiation (PEComa). The patient received adjuvant chemotherapy and radiotherapy after surgical resection, along with monitoring through computed tomography (CT) scans. Three months later, pulmonary metastasis was detected, but both the cutaneous PEComa in the left upper limb and the pulmonary metastatic lesions were stably controlled under active management and treatment. This is a rare case worth reporting and studying, and therefore, we conducted a long-term follow-up, and we hope to provide help for the clinical treatment of PEComa.